Peroxiredoxin-2: a novel regulator of iron homeostasis in ineffective erythropoiesis - Matte, Alessandro; Mueller, Sebastian; Silva, Ines (Antioxidants & redox signaling, 2018)
Aims: Iron overload (IO) is a life-threatening complication of chronic hemolytic disorders such as β-thalassemia. IO results in severe cellular oxidative damage, leading to organ failure. Peroxiredoxin-2 (Prx2), a typical 2-cysteine-(Cys)-peroxiredoxin, is an important component of the cytoprotective system, but its response to IO is still to be fully defined.Results: We studied the effects of IO on Prx2-knockout mice (Prx2−/−). The absence of Prx2 enhanced toxicity due to IO on erythropoiesis. We found that IO failed to induce the typical hepcidin (Hamp) upregulation in Prx2−/− mice due to its failure to activate the signal transducer and activator of transcription-3 (STAT3) with intact Jak2 signaling. In Prx2−/− mice, the loss of Hamp response was also observed after administration of a single dose of oral iron. When lipopolysaccharide (LPS) was used to explore IL6-STAT3 activation in Prx2−/− mice, STAT3 activation and Hamp upregulation were once again defective. Treatment with PEP-fusion-recombinant-Prx2 (PEP Prx2) significantly increased STAT3 activation with upregulation of Hamp expression in both IO- and LPS-exposed Prx2−/− mice. We also confirmed the beneficial effects of PEP Prx2 on Hamp expression through STAT3 activation in β-thalassemic mice.Innovation: We propose that Prx2 plays a key role in responding to cytotoxicity of IO, directly targeting STAT3-transcriptional factor in a Jak2-independent fashion and regulating Hamp in response to canonical stimuli.Conclusion: Collectively, our data highlight a novel role of Prx2 in iron homeostasis. Prx2 is a key cytoprotector against IO that is induced either by iron supplementation or due to chronic hemolysis as in β-thalassemia. Prx2 is required to support STAT3 transcriptional activity and regulation of Hamp expression. Antioxid. Redox Signal. 28, 1-14.
Published online:1 Jan 2018
Gesehen am 19.06.2018